Study of the Prevalence of Opportunistic Mycoses in Pulmonary Tuberculosis Patients in Homs City: Study of The Prevalence of Opportunistic Mycoses in Pulmonary Tuberculosis Patients in Homs City (Journal of Hama University, 2022)
In recent years, fungal infections are on the rise due to various predisposing factors such as patients on steroids, HIV infection and long term administration of antibiotics that occurs in some diseases like tuberculosis. Candida spp exists as part of normal flora, when host resistance is lowered, it transforms to be pathogenic as a result of their virulence factors such as the ability to adhesion to the surfaces of epithelial cells, and the production of enzymes that digest fats and proteins. They take advantage of the weak immunity of the body in their pathogenicity, so they are called opportunistic fungi. This study aimed to evaluate the prevalence of opportunistic candidiasis in pulmonary tuberculosis patients in Homs city and determine the most common fungus that causes these infections.  a cross sectional study was conducted on 80 pulmonary tuberculosis patients during the period from December 2020 to August 2021. Sputum samples were collected from patients and laboratory measurements were performed within two hours of collection, including: Direct microscopic examination and culturing. Then microscopic and macroscopic examination of colonies and biochemical tests were conducted to determine the fungus species and type.out of 80 patients (51 males and 29 females), mean age 42±15.7 years, results showed the presence of fungal infections (molds and yeasts) in 55% of them.Candida spp was the predominant cause of infections (36% of patients were positive), and the most prevalent type is Candida albicans with a percentage of 62.1%, followed by Candida krusei with 24.1%, Candida tropicalis with 10.3% and Candida dubliniensis.Smoking cigarettes was significant risk factor for developing pulmonary fungal infections (p0.05).Findings of this study revealed a high prevalence of pulmonary candidiasis in TB patients, which are often neglected despite their seriousness. Appropriate measures must be taken to detect and treat it, and avoid complications and deaths that it may cause.
Keywords: Tuberculosis, Opportunistic Pulmonary Mycosis, Candida.